Anomaly Detection Techniques Causes and Issues - Sandhya Madhuri, G.; M. Usha Rani, Dr. (International Journal of Engineering and Technology, 2018)
Anomaly means something which is not normal. Any data point which deviates or placed in distance from all other normal data points is an anomaly. That is why anomalies are also called as outliers.Â Anomaly detection is also called as deviation detection because anomalous objects have attribute values that are different from all other normal data objects. In this paper we have discussed about various causes of anomalies, anomaly detection approaches and also issues that are to be taken care during finding out the best technique for anomaly detection.